DETERMINAN KINERJA MANAJERIAL PT PLN (PERSERO) KOTA LANGSA - Teuku Triananda; Meutia, Tuti (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2024)
This research aims to determine the effect of participation in budget preparation, quality of human resources, and organizational commitment on managerial performance at PT. PLN Persero Langsa City. The sampling technique used in this research is non-probability. The data analysis method used is the multiple linear regression equation, hypothesis testing using the t test, F test, and determination test (R2). The research results obtained Y = 0.416 + 0.936X1 + 0.337X2 + 0.417X. It can be stated that participation in budget preparation has a significant effect on managerial performance at PT. PLN Persero Langsa City, the quality of human resources has a significant effect on managerial performance at PT. PLN Persero Langsa City. Organizational commitment has a significant influence on managerial performance at PT. PLN Persero Langsa City. The results of the F test show that F sig < α 5% (0.000 <0.005) can be stated that participation in budget preparation, quality of human resources, organizational commitment simultaneously have a significant effect on managerial performance at PT. PLN Persero Langsa City. The results of the coefficient of determination (R2) obtained a result of 47.8%. Participation in Budget Preparation, Quality of Human Resources, and Organizational Commitment influence managerial performance at PT. PLN Persero Kota Langsa and the remaining 52.2% are influenced by other variables not examined in this research such as Compensation, Leadership, Incentives, Discipline, Motivation and Work Environment.